Intermittent induction of HIF-1α produces lasting effects on malignant progression independent of its continued expression. - Hyunsung Choi; David L Gillespie; Shauna Berg; Christopher Rice; Sandrine Couldwell; Jie Gu; Howard Colman; Randy L Jensen; L Eric Huang (PLoS ONE, 2015)
Dysregulation of hypoxia-inducible transcription factors HIF-1α and HIF-2α correlates with poor prognosis in human cancers; yet, divergent and sometimes opposing activities of these factors in cancer biology have been observed. Adding to this complexity is that HIF-1α apparently possesses tumor-suppressing activities, as indicated by the loss-of-function mutations or even homozygous deletion of HIF1A in certain human cancers. As a step towards understanding this complexity, we employed 8-week intermittent induction of a stable HIF-1α variant, HIF1α(PP), in various cancer cell lines and examined the effects on malignant progression in xenografts of immunocompromised mice in comparison to those of HIF2α(PP). Although 8-week treatment led to eventual loss of HIF1α(PP) expression, treated osteosarcoma U-2 OS cells acquired tumorigenicity in the subcutaneous tissue. Furthermore, the prior treatment resulted in widespread invasion of malignant glioma U-87 MG cells in the mouse brain and sustained growth of U-118 MG glioma cells. The lasting effects of HIF-1α on malignant progression are specific because neither HIF2α(PP) nor β-galactosidase yielded similar effects. By contrast, transient expression of HIF1α(PP) in U-87 MG cells or constitutive expression of HIF1α(PP) but not HIF2α(PP) in a patient-derived glioma sphere culture inhibited tumor growth and spread. Our results indicate that intermittent induction of HIF-1α produces lasting effects on malignant progression even at its own expense.